KOMUNIKASI PERSUASIF PADA HUMAS PALANG MERAH INDONESIA (PMI) DALAM MENINGKATKAN KESADARAN MASYARAKAT UNTUK DONOR DARAH - Malika Alia Jelita; Haryo Kusumo Aji; Estu Widiyowati; Muadz Muadz (Solidaritas, 2025)
This study, entitled "Persuasive Communication by the Indonesian Red Cross Public Relations Unit in Raising Public Awareness of Blood Donation," is a topic of discussion. Low public awareness of blood donation remains a serious problem in various regions, including Grobogan Regency. Data shows that the number of voluntary donors is insufficient to meet the increasing annual need for blood, resulting in blood supply often not being balanced with demand. This situation creates problems in healthcare services and even poses a risk to patient safety. This study aims to determine and analyze how persuasive communication is used by the Indonesian Red Cross (PMI) Public Relations Unit in Grobogan Regency to raise public awareness of blood donation. The study used a descriptive qualitative method with a case study approach, involving interviews with public relations personnel and the community, and documentation as data sources. This study utilizes Burgoon and Huffiner's persuasive communication theory as a conceptual foundation, focusing on the components of the communicator, message, media/channel, recipient, and communication effects. The research results show that PMI Public Relations plays a role as a communicator, crafting persuasive messages using both rational (medical facts, benefits of blood donation) and emotional (humanitarian values, empathy) approaches. These messages were delivered through direct communication (public outreach), print media (banners, brochures), and digital media (Instagram, Facebook, and WhatsApp). Public responses varied, but the majority indicated increased understanding, growing awareness, and active participation in blood donation activities. The persuasive messages were crafted by emphasizing cognitive, affective, and conative aspects, in accordance with the Burgon & Huffner framework, combining factual information and emotional appeal to influence public knowledge, attitudes, and behavior. Public responses varied, but most demonstrated positive changes in the form of increased understanding, growing empathy, and active participation in blood donation activities. These findings confirm that credible, systematic, and adaptive persuasive communication can strengthen PMI's positive image and encourage community involvement. Thus, a persuasive communication strategy is an important instrument in maintaining blood stock availability while building social and humanitarian solidarity.   Keywords: Persuasive Communication, Public Relations, Indonesian Red Cross, Public Awareness.